2017
DOI: 10.1037/cpp0000214
|View full text |Cite
|
Sign up to set email alerts
|

Integrating early childhood screening in pediatrics: A longitudinal qualitative study of barriers and facilitators.

Abstract: Pediatric settings are increasingly called upon to implement early childhood developmental and behavioral health screening as an early identification and health promotion strategy. Understanding the dynamic barriers and facilitators of implementation at various stages will help implementers plan for and address these factors in support of high quality implementation. Our research supported this goal by analyzing longitudinal, qualitative data. There were 128 semistructured interviews conducted with pediatric c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…Implementation science is a new field and one not often utilized, to date, in pediatric psychology. The findings of the current study are consistent with those reported with respect to early childhood screening in pediatrics (Silver et al, 2017). Based on semistructured interviews with providers in primary care settings, screening procedures and flow, clinic infrastructure, and staffing were important potential concerns.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Implementation science is a new field and one not often utilized, to date, in pediatric psychology. The findings of the current study are consistent with those reported with respect to early childhood screening in pediatrics (Silver et al, 2017). Based on semistructured interviews with providers in primary care settings, screening procedures and flow, clinic infrastructure, and staffing were important potential concerns.…”
Section: Discussionsupporting
confidence: 92%
“…The effect of the size of a setting may also be important. Silver et al (2017) suggest that smaller sites may be more flexible and accommodate changes in practice more easily than larger sites, which have more competing demands to juggle. Some centers with small oncology programs may face different issues as they would be using the PAT less frequently and may have additional needs for training or integration of it into staffing and workflow.…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of such efforts should not be spontaneous. Implementation science provides a reliable framework for integrating practices into routine care by identifying the necessary conditions for high-quality implementation (Silver et al, 2017). This is particularly important when developing processes with considerations for diverse populations.…”
Section: Aces and Childhood Developmentmentioning
confidence: 99%
“…The final article in this special issue provides longitudinal qualitative data gathered during a grant-funded initiative to integrate early childhood developmental and behavioral screenings into pediatric primary care. In this article, Silver and colleagues (2017) detail the perspectives of both clinical providers and implementation study staff regarding barriers and facilitators to screening acceptance, uptake and sustainability across time. Their extensive data, drawn from multiple perspectives, results in valuable information for pediatric psychologists (and others) endeavoring to implement systemic changes to clinical care models within pediatric health care systems.…”
Section: Implementing Clinical Initiatives In the Health Care Settingmentioning
confidence: 99%